A Modified Reach-to-Grasp Task in a Supine Position Shows Coordination Between Elbow and Hand Movements After Stroke - Broome, Kate; Hudson, Irene; Potter, Kaitlyn; Kulk, Jason; Dunn, Ashlee; Arm, Jameen; Zeffiro, Tom; Cooper, Gavin; Tian, Huiqiao; van Vliet, Paulette (Frontiers in Neurology, 2019)
Objective: A modified reach-to-grasp task has been developed for the purpose of investigating arm-hand coordination in a supine position in the functional magnetic resonance imaging environment. The objective of this study was to investigate the kinematics of the reach-to-grasp task, in stroke and healthy participants. Design: Observational cohort study. Setting: Movement laboratory. Participants: Ten stroke participants and ten age-matched healthy participants performed ten repetitions of the modified reach-to-grasp task in two conditions – a natural condition and a standardised condition in a splint. Intervention: Not applicable. Main Outcome Measures: Kinematic variables of start time of transport, start time of aperture, movement duration, time of peak velocity (PV), percentage time of PV, peak deceleration (PD), percentage time of PD, peak aperture (PA), time of PA and percentage time of PA were recorded. The correlation between key events in the grasp and transport trajectories were investigated. Performance between conditions and groups were compared. Results: Both groups demonstrated a significant correlation between the start time of aperture and the start time of transport and between the time of PA and PV in both conditions. A significant correlation was found between the time of PA and the PD in both conditions for the healthy group, but in neither condition for the stroke group. Movements by participants with stroke had a significantly longer movement duration, a smaller PV, and an earlier absolute time of PV and PD, and an earlier percentage time of PV and PD. They also had a smaller aperture than healthy participants. Wearing the splint resulted in a significantly higher PV, later absolute and percentage time of PV, PD and PA, and a smaller PA compared to moving without the splint. The timing of transport variables time to peak velocity and time to peak deceleration, were strongest determinants of movement duration. Conclusion: The modified reach-to-grasp movement performed without the constraint of the splint, demonstrates similar motor control and coordination between the grasp and transport components of reach-to-grasp as in seated reach-to-grasp. This provides new task that may be used to explore reach-to-grasp in the fMRI environment.